2006
DOI: 10.1021/ja0607990
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between HOMO Alignment and Contact Resistance in Molecular Junctions:  Aromatic Thiols versus Aromatic Isocyanides

Abstract: Understanding electron transport in metal-molecule-metal (MMM) junctions is of great importance for the advancement of molecular electronics. Critical factors that determine conductivity in a MMM junction include the nature of metal-molecule contacts and the electronic structure of the molecular backbone. We have studied the electronic transport property and the valence electronic structure on rigid, conjugated oligoacenes of increasing length with either thiol (-S) or isocyanide (-CN) linkers using conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
358
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(377 citation statements)
references
References 25 publications
18
358
1
Order By: Relevance
“…2 Studies on various -conjugated molecules have been performed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The molecules, with delocalized electrons due to sp 2 hybridized carbon atoms, exhibit a smaller energy gap between the highest occupied molecular orbital ͑HOMO͒ and the lowest unoccupied molecular orbital ͑LUMO͒. For -conjugated molecules longer than ϳ3 nm hopping conduction was observed.…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%
“…2 Studies on various -conjugated molecules have been performed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The molecules, with delocalized electrons due to sp 2 hybridized carbon atoms, exhibit a smaller energy gap between the highest occupied molecular orbital ͑HOMO͒ and the lowest unoccupied molecular orbital ͑LUMO͒. For -conjugated molecules longer than ϳ3 nm hopping conduction was observed.…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%
“…In these cases, the conduction is LUMO controlled. 95,96 We can also observe that sharper peaks are obtained in the case of nitrile (−CN) containing devices TPCN because a weaker interaction between such groups and gold surfaces is expected. As in the case of TPS, only one eigenchannel is open in the voltage window studied.…”
Section: A Influence Of the Anchoring Groupsmentioning
confidence: 82%
“…This is a reasonable assumption due to the low distortion of the Au arrangement expected. [94][95][96] While SIESTA supports the spin-polarized treatment of electrons, taking into account the nature of our system we employed only unpolarized calculations in this study. With these initial conditions we found that a distance from sulphur to the Au contact site of 2.25Å, corresponding to an S-Au distance of 2.82Å, presents a minimum energy.…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Without discussion the most widely used anchoring group is thiol Haiss et al, 2008;Haiss et al, 2009;Huang et al, 2006;Huang et al, 2007a;Huang et al, 2007b;Li et al, 2007b;Li et al, 2006a;Ulrich et al, 2006;Xu et al, 2003a;Xu et al, 2005;Xu & Tao, 2003), although pyridine (Xu et al, 2003a;Xu & Tao, 2003), isocyanide (Beebe et al, 2002;Kiguchi et al, 2007;Kim et al, 2006a), selenium (Patrone et al, 2003a;Patrone et al, 2003b;Yasuda et al, 2006), amine Hybertsen et al, 2008;Kamenetska et al, 2009;Kiguchi et al, 2008;Park et al, 2007;Park et al, 2009;Quek et al, 2007;Quek et al, 2009;Quinn et al, 2007;Venkataraman et al, 2006a;Venkataraman et al, 2007;Venkataraman et al, 2006b), phosphines Park et al, 2007) and carboxylate Martín et al, 2008) have proved to provide enough binding strength to yield a stable contact. In most of these works, the metallic electrodes that the molecule bridges are made of gold, but some recent reports showed the utility of platinum electrodes for those purposes (Kiguchi et al, 2007;Kiguchi et al, 2008).…”
Section: Experimental Measurementsmentioning
confidence: 99%